2023
DOI: 10.3390/app13031996
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Potential Food Application of Lima Beans (Phaseolus lunatus L.), an Underutilized Crop

Abstract: The world is facing the global challenges of insecurity, poverty and climate change, which can impede food availability, production and nutritional security. Due to these factors, the production and availability of crop species such as legumes, pulses and cereals are declining, while some are gradually becoming extinct, which affects consumption. To meet global food demands, efforts should be geared towards promoting the cultivation and utilization of underexploited and neglected crops, which have the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 70 publications
0
12
0
2
Order By: Relevance
“…Its dietary fiber content also aids in preventing degenerative and chronic diseases, such as diabetes, cancer, obesity, neoplasms, and cardiovascular diseases (Toklu et al 2021). Furthermore, studies indicate that factors such as phytic acid, tannins, trypsin inhibitor, and hydrogen cyanide, which are present in Phaseolus but not in cereals, can be partially or fully eliminated through common household or industrial processing methods such as cooking, soaking, roasting, and husking (Adebo 2023;El-Gohery 2021). From salads to soups and stews, "Pallar" is widely used in Peru's varied culinary landscape and is a staple ingredient.…”
Section: Food Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Its dietary fiber content also aids in preventing degenerative and chronic diseases, such as diabetes, cancer, obesity, neoplasms, and cardiovascular diseases (Toklu et al 2021). Furthermore, studies indicate that factors such as phytic acid, tannins, trypsin inhibitor, and hydrogen cyanide, which are present in Phaseolus but not in cereals, can be partially or fully eliminated through common household or industrial processing methods such as cooking, soaking, roasting, and husking (Adebo 2023;El-Gohery 2021). From salads to soups and stews, "Pallar" is widely used in Peru's varied culinary landscape and is a staple ingredient.…”
Section: Food Securitymentioning
confidence: 99%
“…In addition, mineral composition ranges have been reported for calcium (11.04–360.73 mg/100 g), phosphorus (74.95–359.73 mg/100 g), iron (3.29–18.54 mg/100 g), sodium (53.87–187.46 mg/100 g), Zn (3.20–4.17 mg/100 g) and potassium (38.21–1373.29 mg/100 g), the latter being predominant in Lima bean cultivars (Table 3). These variations in nutritional and mineral composition may be attributed to climatic factors, growth stages, and agronomic conditions of the variety (Adebo 2023). On the other hand, according to studies reported by Ccala Sucasaca and Ramirez Carrasco (2021), the “Pallar de Ica” contains significant amounts of limiting amino acids (lysine and methionine) and essential amino acids (valine and phenylalanine).…”
Section: Food Securitymentioning
confidence: 99%
“…Lima beans are known for their high protein, carbohydrate, fat, and micronutrient sources needed by the body and contain a variety of essential amino acids that plays an important role in the growth process (Ishaya et al, 2019;Van Vught et al, 2013). Lima beans contain the amino acids leucine, isoleucine, lysine, arginine, and glutamine, which play a role in growth and development (Adebo, 2023). Arginine is an amino acid involved in growth hormone production, which regulates growth and metabolism (Kanaley, 2008).…”
Section: Morphometric Analysismentioning
confidence: 99%
“…Adebo, 2023; Bonita G et al, 2020;Adewole et al, 2021). Linoleic acid and palmitic acid are the two most important components.…”
mentioning
confidence: 99%
“…As a legume crop, lima bean seeds are a good source of dietary protein, carbohydrates, fiber, and minerals, particularly iron (Bonita et al., 2020). Lima bean is grown across a wide range of environments, including humid tropical, arid, and temperate ecological zones (Adebo, 2023). Global production of lima bean is difficult to assess because many countries and the Food and Agriculture Organization (FAO) of the United Nations do not keep separate statistics on lima bean production.…”
Section: Introductionmentioning
confidence: 99%